2021
DOI: 10.3390/healthcare9020199
|View full text |Cite
|
Sign up to set email alerts
|

Panic and Trust during COVID-19: A Cross-Sectional Study on Immigrants in South Korea

Abstract: In the COVID-19 pandemic, marginalized groups like migrants are disproportionately affected. As panic, fear of neglect, and mistrusting institutions in these groups are presumed to be apparent, their detachment to health services still needs to be investigated. This study comparatively analyzed the level of panic and trust between South Koreans and immigrants who are living within highly affected areas of South Korea. Mann–Whitney-U-Test and Pearson correlation showed panic is more pronounced in the Korean gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Isolation could emotionally reactivate a traumatic experience in which fundamental rights were truncated, as well as other psychological problems such as depression, anxiety, fear and confusion, among others [ 1 ]. Moreover, a fear of disease has been linked to mental health, which has also been reported in refugee cases in the literature [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 94%
“…Isolation could emotionally reactivate a traumatic experience in which fundamental rights were truncated, as well as other psychological problems such as depression, anxiety, fear and confusion, among others [ 1 ]. Moreover, a fear of disease has been linked to mental health, which has also been reported in refugee cases in the literature [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 94%
“…I waited for three days before my clothes arrived. (Mark, Filipino, male, 29 years old, factory worker) Perhaps because they were compensated during the quarantine and fully insured by the National Health Insurance, James and Mark placed much trust on the host country's medical governance (see a similar situation in South Korea, Yoon et al, 2021) in comparison with the chaotic situation in their home country. While James seemed tolerant of the government's order on migrant immobility, he became agitated when describing how the factory removed their luggage and belongings from the dormitory while they were in quarantine facilities.…”
Section: Migrants' Narratives Of Immobilitymentioning
confidence: 99%
“…Both groups of subjects, however, reported that they rarely experienced increased heart rate, sweating, or difficulty breathing due to the spread of the virus. In comparative analyzes, Koreans more often felt temporary terror, fear, worry, loss of control, fear of death and presented somatic symptoms [33].…”
Section: Panic Disorders In the Covid-19 Pandemicmentioning
confidence: 99%